Relationship between diabetes training session, nurse factors and competencies in diabetes care - Lamasan, Judy P.
The challenge for competence in care has constantly been emphasized to improve patient care outcomes. Several factors however, have been observed to effect the quality of care for diabetic patients in terms of knowledge, skills and attitude. These are in the areas of competence after graduation from the nursing curriculum and implementation of nursing standards in diabetes care. While many studies about diabetes care and the cognitive level has been done, there is a dearth in the area of skills and attitude.{{{{The study aimed to determine two objectives: first, the difference in the competence level in diabetes care between nurses who participated and those who did not participate in the diabetes training session; second: the relationship between nurse factors (such as age, work experience as a nurse, education and training, diabetes involvement) and the competence level in diabetes care.{{{{The experimental, posttest-only-control group design was used. The study was conducted at Ospital ng Maynila Medical Center and subjects were nurses assigned in the clinical areas where diabetic patients were admitted. The study utilized two groups, the study and control. Fifty-four nurses participated in the study , 28 in the control group and 26 in the study group. The subjects were randomly assigned to either group. The study group was given the Diabetes Training Session (DTS) while the control group followed the routine procedure. Both groups were subjected to the post-tests.{{{{The results of the preliminary survey of learning needs of nurses provided the basis for the development of a competency-based program on diabetes training. The DTS is structured , following the essentials for a competency-based program. The diabetes training session include the topics on: nature of diabetes, blood glucose monitoring, insulin administration, and hypoglycemia. These topics focus on the survival knowledge and skills to address the priority learning needs of nurses in the acute care of diabetes patients. There were three sessions provided to train the nurses in the study group. Each session lasted for about 2 hours. The instruments used were Nurse Profile, Diabetes Knowledge Test (DKT), Tests for Skills on Blood Glucose Monitoring (BGM) and Insulin Administration (IA), and the Diabetes Attitude Scale (DAS).{{{{To provide the general profile of the nurse ...